Lactic acid fermentation of balao-balao (rice-shrimp mixture) - Solidum, Ma. Haidea Tirol
Balao-balao prepared according to the proceure of Arroyo, et al. (1977) was found to be fermented at tropical room temperature by a sequence but overlapping growth of lactic acid bacteria. Fermentation was initiated by streptococcus sp., followed by Leuconostoc sp. which was soon outnumbered by Pediococcus sp. The ten-day fermentation was completed by the high acid-producing homofermentative Lactobacillus sp. The activity of these lactics caused an increase in the titrable acidity of the product with a concomitant decrease in pH. During the ten-day fermentation, however, differences in the microbial flora and pH-titrable acidity values among the three batches of balao-balao prepared at different occasions were noted. Volatile acidity of the ten-day old samples also differed. These could be due to differences in fermentation temperature and salt concentration. In all three batches, however, the fermentation was practically homofermentative due to the predominance of Pediococci and Lactobacilli. Inoculation of newly-prepared balao-balao with the high homofermenter Lactobacillus sp. obtained from a previous fermentation was found to increase ferementation rate without causing a delerious effect on sensory qualities. Inoculation with other lactics isolated from fermenting balao-balao did not give a substantial improvement over the control. These may indicate therefore, the beneficial effect of inoculation with Lactobacilli.